2010
DOI: 10.3109/03009741003685632
|View full text |Cite
|
Sign up to set email alerts
|

Limited value of ultrasound assessment in patients with poor outcome after carpal tunnel release surgery

Abstract: Reduction of the median nerve cross-sectional area at tunnel inlet at 3 months after carpal tunnel release was similar in patients reporting cure or great improvement and in those with slight or no improvement. Ultrasonography is of limited value in assessment of patients with poor outcome after median nerve release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
2
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 9 publications
3
39
2
6
Order By: Relevance
“…This might be explained by the larger amount of soft tissue and structures surrounding the tibial nerve, leading to more diffusely spread pressure. In patients with idiopathic carpal tunnel syndrome and without diabetes, release of the flexor retinaculum results in a decrease of CSA (27)(28)(29). One study showed an increase of CSA and T/W ratio (30).…”
Section: Discussionmentioning
confidence: 99%
“…This might be explained by the larger amount of soft tissue and structures surrounding the tibial nerve, leading to more diffusely spread pressure. In patients with idiopathic carpal tunnel syndrome and without diabetes, release of the flexor retinaculum results in a decrease of CSA (27)(28)(29). One study showed an increase of CSA and T/W ratio (30).…”
Section: Discussionmentioning
confidence: 99%
“…Significant decreases in cross-sectional area have been noted, and decreased cross-sectional area has been correlated with improvement in symptom scores and electrodiagnostic parameters [5356]. However, another study found no significant difference in cross-sectional area between patients with favorable and unfavorable outcomes, although cross-sectional area was decreased in both groups [57]. Additional investigations into the reliability of sonographic parameters for predicting outcomes are needed.…”
Section: Compressive Neuropathymentioning
confidence: 99%
“…For example, is a reduced cross‐sectional area a result of atrophy or reduced edema and improvement? Although these findings seem to be a part of the pathologic process, are these a result or an etiologic factor in CTS [3]? Using these findings as an outcome measure, therefore, is problematic, and furthermore, because we are treating a clinical syndrome composed of symptoms and signs, it is much easier and more logical to evaluate clinical improvement as an outcome measure. 2In a modality that is reliant on the operator, can we quantify these changes in a meaningful way?…”
Section: Resultsmentioning
confidence: 99%